Territorializing the Arctic: Problem of Ice in International Law - Assaf, Alaa (Право. Журнал Высшей школы экономики, 2023)
Following the 2021 Suez Canal obstruction, humanity is now in search of safer and better functioning maritime trade routes, and the icy Arctic turns out to be one of the key candidates. The article contributes to the current debate concerning the status of ice in International Law, the legal status of which remains unclear, stuck in a limbo between the law of the terrain and the law of the sea. The methodology includes reconfiguring the meaning of ‘territory’ under International Law through conducting an evolutionary interpretation to provide grounds for the existence of a ratione materiae type of territory, supported by related domestic and international legal instruments of Alpine and Arctic States. The article outlines useful elements from similar experiments on the measurement of ice features employed in the process of the Alps border demarcation and administration. In conclusion, a sketch of a ‘functional’ Arctic is drawn to suit a world aiming at a sustainable human-nature relationship. The paper aims to introduce ‘ice’ as a legally valid criterion under the law of territory that can be applied in sovereignty disputes on a regular rather than sui generis basis. It demonstrates the fallacy of the static conception of territory in the modern day, particularly when applied in a dynamic environment such as the Arctic, while also stressing the importance of multidisciplinary learning and its critical role in advancing legal theory in domains considered to be the most normatively rigid, such as territorial sovereignty.